Effect of chosen factors on milk yield, basic composition and somatic cell count of organic milk of Brown short-haired goats - Šárka Králíčková; Jan Kuchtík; Radek Filipčík; Táňa Lužová; Květoslava Šustová (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2013)
Effect of stage of lactation (SL), parity (PA), litter size (LS) and month of kidding (MK) on daily milk yield, basic composition and somatic cell count of organic goat milk were evaluated using 32 goats of Brown short-haired breed which were reared on an organic farm in Olešenka. Goats were on the 1st (n = 15), 2nd (n = 10) and 3rd (n = 7) lactation; 15 of them gave birth to singles and 17 to twins. Kidding occurred in January (n = 5), February (n = 13) and March (n = 8). During the experiment all goats were reared on permanent pasture, in one flock and under the identical conditions. The PA had a significant effect on all monitored parameters; also the SL had a significant effect on all monitored parameters except SCC. Systematic factors LS and MK had a significant effect only on DMY and SCC; on the other hand, these factors had no significant effect on basic milk composition. The milk fat was the most variable component of the milk. On the other hand the lactose content was during lactation very well-balanced. SCCs were relatively low which indicates good health status of mammary gland. The highest DMY, SCC and contents of basic milk components, except lactose, were found in goats on PA2. The higher DMY was expected in goats with twins compared to goats with singles, but the opposite trend proved to be true.